An educational program about premarital screening for unmarried female students in King Abdul-Aziz University, Jeddah - Nahla Khamis Ragab Ibrahim; Hussein Al-Bar; Ali Al-Fakeeh; Jawaher Al Ahmadi; Mahdi Qadi; Adnan Al-Bar; Waleed Milaat (Elsevier, 2011)
Summary: The present study was conducted to assess knowledge and attitude of unmarried female students in King Abdul-Aziz University (KAU) towards premarital screening (PMS) program, to determine predictors of high students' knowledge scores and to improve their knowledge about PMS through conduction of an educational campaign. Multi-stage stratified random sample method was used with recruitment of 1563 students from all faculties of KAU, during the educational year 2008-2009. The Pre-test included 30 knowledge items and 14 attitude statements with student's response through a 5-point Likert scale. Health education was conducted using audiovisual aids through pre-designed educational materials. Statistical analysis was done by SPSS version 16. Results: Students' knowledge about the program was generally low before the educational campaign. The predictors of high knowledge scores were being a health science student (aOR = 4.15; 95% CI: 2.97-5.81), age ≥20 years (aOR = 2.78; 95% CI: 2.01-3.85), family history of hereditary diseases and income ≥10,000 SR/month. Regarding attitude, almost all students (99.0%) agreed on the importance of PMS. After the educational program, students' knowledge about PMS was markedly improved. The mean students' knowledge score was 9.85 ± 5.36 in Pre-test and improved to 18.45 ± 4.96 in Post-test, with a highly statistical significant difference (paired t = 25.40, p < 0.000). Conclusion and recommendations: The educational program was successful in improving students' knowledge about the PMS. Conduction of similar educational programs and adding PMS in the curriculum of secondary and university education are recommended. Keywords: Premarital, Screening, University students, Educational program, Jeddah, KSA